Infantile neuroaxonal dystrophy in a pair of Malaysian siblings with progressive cerebellar atrophy: Description of an expanded phenotype with novel PLA2G6 variants. (January 2020) - Li, Limin; Fong, Choong Yi; Tay, Chee Geap; Tae, Sok Kun; Suzuki, Hisato; Kosaki, Kenjiro; Thong, Meow-Keong
Highlights: Progressive cerebellar atrophy may be a useful feature to direct focused diagnostic investigations in infantile neurodegenerative disorders. Our case is the first to report auditory neuropathy as a feature of INAD and widens the clinical phenotype of INAD. Exome sequencing is a useful tool in rare undiagnosed diseases. Genetic counseling is essential to help families with hereditary conditions. Abstract: Infantile neuroaxonal dystrophy 1 (INAD) (OMIM #256600) is a rare infantile onset neurodegenerative disease characterised by neuroregression and hypotonia, evolving into generalized spasticity, blindness and dementia. We report our diagnostic approach of a pair of siblings with psychomotor regression, hypotonia, optic atrophy and auditory neuropathy. The brain magnetic resonance imaging (MRI) showed progressive cerebellar atrophy. Genetic testing of the PLA2G6 confirmed presence of compound heterozygous novel mutations. As the variant c. 196C>T (p.Gln66X) was a truncating variant, it was considered as pathogenic while the variant c. 2249G>A (p. Cys750Tyr) was considered as "likely pathogenic" by bioinformatics analyses. Our patient expands the clinical phenotype of INAD as it described the first South-East Asian patient with INAD-associated auditory neuropathy. Our report highlights the importance of increased awareness of this condition amongst clinicians, the use of deep phenotyping using neuroimaging and the clinical utility of gene sequencing test in the delineation of syndromes associated with infantile neurodegenerative disease.